Digital Marketing’s Impact on MSME Performance: Median Influence of Digital Literacy and Brand Awareness - Yekti Asmoro Kanthi; Bagus Kristomoyo Kristanto; Roby Firnando Yusuf (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study analyzes the influence of digital marketing on digital literacy, brand awareness, and the performance of MSMEs in Malang City, while investigating the mediating roles of literacy and awareness. Research Design & Methods: A quantitative research design was employed using survey data collected from 392 MSME actors selected through purposive sampling. Structural Equation Modeling (SEM) was applied to examine the direct and indirect relationships among digital marketing, digital literacy, brand awareness, and MSME performance. Findings: The results reveal that digital marketing has a significant positive effect on digital literacy and brand awareness. Additionally, both digital literacy and brand awareness significantly enhance MSME performance. However, digital marketing does not directly influence performance; its effect becomes significant only through the mediating mechanisms of digital literacy and brand awareness. Implications & Recommendations: The findings highlight that the impact of digital marketing is entirely contingent upon the readiness of MSME actors and their market positioning. Theoretically, this reinforces the importance of integrating digital competencies into strategic marketing frameworks. Socially, the results advocate for community-based digital mentoring to bridge the economic divide. Practically, targeted support from policymakers (local government) is crucial for enhancing digital skills and brand-strengthening capabilities to ensure long-term MSME sustainability. Contribution & Value Added: This study provides empirical evidence on the role of digital marketing in enhancing digital literacy and brand awareness as key mechanisms that drive MSME performance, while offering practical insights for practitioners and policymakers to strengthen digitally based business strategies.